2020
DOI: 10.3390/foods9101397
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for the Identification of Fresh and Processed Pagellus erythrinus Species against Frauds

Abstract: The commercialization of porgies or seabreams of the family Sparidae has greatly increased in the last decade, and some valuable species have become subject to seafood substitution. DNA regions currently used for fish species identification in fresh and processed products belong to the mitochondrial (mt) genes cytochrome b (Cytb), cytochrome c oxidase I (COI), 16S and 12S. However, these markers amplify for fragments with lower divergence within and between some species, failing to provide informative barcodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Sixteen complete Sparidae mitogenome sequences were analyzed in this study, as reported in Ceruso et al [ 21 ]. Eleven specimens of D. dentex from Food and Agriculture Organization (FAO) area 37 were sampled ( Table 1 and Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen complete Sparidae mitogenome sequences were analyzed in this study, as reported in Ceruso et al [ 21 ]. Eleven specimens of D. dentex from Food and Agriculture Organization (FAO) area 37 were sampled ( Table 1 and Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The fish species other than Dentex dentex were carefully chosen with the aim to include (i) those used to substitute Dentex dentex (e.g., Dentex gibbosus ), (ii) phylogenetically related sparid species (e.g., Pagellus erythrinus ) [ 18 ], and (iii) other species commonly found in Mediterranean fish markets. Ten specimens of Pagellus erythrinus , the most genetically close to Dentex dentex among sparids [ 21 ], were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most used molecular markers, mitochondrial genes, such as Cytochrome b (Cytb), 16S rRNA (16S), Cytochrome Oxidase I (COI) and mtDNA Control Region (CR), have proven to be optimal tools for seafood species authentication. However, while the CR and Cytb have been successfully and widely used to study the genetic population structure [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] rather than to authenticate fish species [ 27 , 28 , 29 ], COI has become the optimal DNA barcode for the identification of animal species [ 30 , 31 , 32 , 33 , 34 , 35 ] and particularly for fish species authentication in seafood products [ 15 , 36 , 37 , 38 , 39 , 40 , 41 ]. Furthermore, researchers have been also encouraged to look for rapid and low-cost molecular strategies to tackle substitution species frauds by large scale screening both using classic and new technologies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, mtDNA undergoes faster evolution making it more effective for the identification of adjacent interspecies (Amaral et al 2017). Cytochrome oxidase subunit I (COI), 16S, and 12S ribosome subunits, as well as cytochrome b are the most widely used mtDNA for DNA barcoding (Ceruso et al 2020;Hanifaturahmah et al 2020). This study used COI gene from mitochondrial DNA as the target gene.…”
Section: Introductionmentioning
confidence: 99%